Critical Thinking Development in Physics Education Through The Implementation of the BW-ExPort Model at Madrasah Aliyah - Nasrun Balulu; Isnawati Isnawati; Supriyadi Supriyadi; Budi Jatmiko; Zulkifli Ahmad; Iqbal Limatahu; Amiruddin Takda (Jurnal Pendidikan Islam, 2026)
Physics practicum activities in Madrasah Aliyah (MA) require learning models that not only strengthen students’ cognitive skills but also integrate character values aligned with Islamic education. This study aims to develop and evaluate the BW-ExPort (Based–Writing–Experimental Report) learning model to improve students’ critical thinking skills during physics practicum activities in MA. Using a Research and Development (R&D) design, the study proceeded through three stages: preliminary study, model development, and field testing. The participants consisted of 82 eleventh-grade students from two MA in North Maluku. Data were gathered through expert validation, classroom observation, and critical thinking assessments, and analyzed using the Rasch model with stacking and racking techniques. Stacking analysis via the Wright Map revealed a clear increase in student ability, shifting from pre-test logits (–3 to 0) to post-test logits (0 to +3), with one student reaching +4. Interpretation and explanation items became easier after the intervention, while evaluation and inference items remained comparatively difficult, indicating the need for additional scaffolding. Racking analysis further confirmed increased item ease, suggesting improved mastery. The BW-ExPort model is valid, practical, and effective in strengthening students’ critical thinking during physics practicum activities. By integrating Islamic scientific ethics such as honesty and responsibility, BW-ExPort offers a culturally grounded and impactful model for digital-based science learning that supports both cognitive growth and character development in Islamic educational settings.